The Evolving Labor Market Impacts of COVID-19 in Developing Countries - Khamis, Melanie; Prinz, Daniel; Newhouse, David; Palacios-Lopez, Amparo; Pape, Utz; Weber, Michael (World Bank, Washington, DC, 2021)
The early labor market impacts of the Coronavirus disease 2019 (COVID-19) pandemic resulted in widespread disruption to livelihoods. Previous analysis showed that between April and July 2020, across a sample of 39 countries, an average of 34 percent of workers stopped work, 20 percent of employees experienced partial or no payments for work performed, and 9 percent changed jobs during the early part of the pandemic. This brief discusses how labor markets have evolved since the initial phase of the crisis in the spring and early summer of 2020. It uses harmonized data from high-frequency phone surveys (HFPS) conducted in 33 developing countries and provides information on the changing labor market impacts of the crisis in these countries from the initial phase of the pandemic in April 2020 through December 2020.